Sejarawan dan persejarahan Melayu - Muhammad Yusof bin Ibrahim (Kuala Lumpur : Tinta Publishers, 2011)
Biography and works of the Malay historians from the 16th to the 20th century.
jilid 1. Warisan & kesinambungan - jilid 2. Tradisi & transformasi .
Includes bibliographical references.
In Malay.
Keywords: Historians -- Malaysia -- Biography; Historiography -- Malaysia; Malaysia -- Historiography